A synthetic control evaluation of the use of pulse oximeters in response to the COVID-19 pandemic in England - Stefano Conti; Paris Pariza; Arne Wolters (PLoS ONE, 2025)
Objectives To measure the impact of the use of pulse oximeters in early detection of oxygen saturation deterioration for patients testing positive with COVID-19 in preventing emergency hospital utilisation and death. This intervention was rolled out across England (part of the United Kingdom) as the COVID Oximetry @home programme. Design Causal inference study informed by linked national administrative and surveillance data-sets to detect the difference in impact of the COVID Oximetry @home programme by comparing areas of the country with high uptake of the programme with areas with low uptake of the programme using generalised synthetic controls. Setting This intervention was rolled out across all Clinical Commissioning Groups (CCGs) in England, administrative geographical areas often aligned with local authorities. All CCGs were invited to submit participation data to the National Health Service in England. Those CCGs that submitted complete data were included in the study. Participants Patients registered with participating CCGs who tested positive for COVID-19, and where either 65 years of age or over, or clinically extremely vulnerable. Outcomes A&E attendances, emergency admissions, admissions into critical care and mortality within 28 days of a positive COVID-19 diagnosis. Results No differences were detected in the rate of emergency hospital use or mortality between CCGs with high uptake and CCGs with low uptake. Conclusion The lack of impact detected on all outcomes of interest may simply be due to an absence of impact. Factors that may have impacted the ability to detect an effect are the low uptake of the programme, heterogeneity in the implementation of the pathway, or design limitations of the study.